2016
DOI: 10.1016/j.wneu.2015.11.061
|View full text |Cite
|
Sign up to set email alerts
|

Extraneural Glioblastoma Multiforme Vertebral Metastasis

Abstract: Glioblastoma multiforme (GBM) is the most common malignant central nervous system tumor; however, extraneural metastasis is uncommon. Of those that metastasize extraneurally, metastases to the vertebral bodies represent a significant proportion. We present a review of 28 cases from the published literature of GBM metastasis to the vertebra. The mean age at presentation was 38.4 years with an average overall survival of 26 months. Patients were either asymptomatic with metastasis discovered at autopsy or presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(70 citation statements)
references
References 40 publications
1
69
0
Order By: Relevance
“…In recent years, increasing evidence has shown that patients with malignant cerebral tumors develop extracranial metastases, especially after a craniotomy or cranial irradiation, and this usually worsens the prognosis. [34][35][36] Given the important roles of LVs in metastasis, we hypothesized that dorsal MLVs contribute to the dissemination of brain tumor cells. To test this, GL261-GFP + or B16-GFP + tumor cells were injected into the cisterna magna (i.c.m.)…”
Section: Prox1-creer T2+ ; R26-tdtomato +mentioning
confidence: 99%
“…In recent years, increasing evidence has shown that patients with malignant cerebral tumors develop extracranial metastases, especially after a craniotomy or cranial irradiation, and this usually worsens the prognosis. [34][35][36] Given the important roles of LVs in metastasis, we hypothesized that dorsal MLVs contribute to the dissemination of brain tumor cells. To test this, GL261-GFP + or B16-GFP + tumor cells were injected into the cisterna magna (i.c.m.)…”
Section: Prox1-creer T2+ ; R26-tdtomato +mentioning
confidence: 99%
“…The ventricles communicate to the spinal cord and this could represent the metastatic route. Metastases to the bone are found in approximately 31% of all extracranial metastases but when it occurs, the most common site is the vertebrae (73% of cases) . Whether these vertebral metastases described in the literature have involved the ventricles of the brain is unknown, but this might be the case due to the direct contact between tumor cells and the cerebrospinal fluid running in the subarachnoid space in the spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Metastases to the bone are found in approximately 31% of all extracranial metastases but when it occurs, the most common site is the vertebrae (73% of cases). 12 Whether these vertebral metastases described in the literature have involved the ventricles of the brain is unknown, but this might be the case due to the direct contact between tumor cells and the cerebrospinal fluid running in the subarachnoid space in the spinal cord. Circulating tumor cells present in the ventricular system could potentially seed in the vertebrae, as supported by observations of metastases to the abdomen in patients with a ventriculo-peritoneal shunt.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Twenty-eight cases of patients with vertebral body metastases are reported in literature;[2] they tend to occur in younger patients (mean age of 38 years) experiencing longer overall survival. The average length survival from diagnosis of spinal metastases was of 10 months.…”
Section: Discussionmentioning
confidence: 99%
“…The average length survival from diagnosis of spinal metastases was of 10 months. [2] Because this tendency is expected to increase long-term survival, survivors should be evaluated for extraneural metastases in their routine follow-up. This case reinforces the few reports presented in literature and highlights the importance of a high index of suspicion and a systemic radio-oncological follow-up in patients with glioblastoma.…”
Section: Discussionmentioning
confidence: 99%